2023
DOI: 10.1111/dom.15305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of finerenone in patients with type 2 diabetes, chronic kidney disease and altered markers of liver steatosis and fibrosis: A FIDELITY subgroup analysis

Nikolaos Perakakis,
Stefan R. Bornstein,
Andreas L. Birkenfeld
et al.

Abstract: AimInvestigating the effect of finerenone on liver function, cardiovascular and kidney composite outcomes in patients with chronic kidney disease and type 2 diabetes, stratified by their risk of liver steatosis, inflammation and fibrosis.Materials and MethodsPost hoc analysis stratified patients (N = 13 026) by liver fibrosis and enzymes: high risk of steatosis (hepatic steatosis index >36); elevated transaminases [alanine transaminase (ALT) >33 (males) and >25 IU/L (females)]; and fibrosis‐4 (FIB‐4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Finerenone, a non-steroidal selective mineralocorticoid receptor antagonist that induces natriuresis with reduced hyperkalaemia compared with steroidal antagonists, potentially provides anti-inflammatory and antifibrotic effects in DKD [153]. Finerenone inhibits MR over-activation and has recently been shown to slow the progression of CKD and reduce the risk of CV events in T2D [173]. In addition, preclinical studies have demonstrated the anti-inflammatory effects of SGLT2 inhibitors empagliflozin and dapagliflozin in association with a reduction in albuminuria and renal fibrosis in DKD [174,175].…”
Section: Agents Targeting Inflammation Oxidative Stress and Fibrosismentioning
confidence: 99%
“…Finerenone, a non-steroidal selective mineralocorticoid receptor antagonist that induces natriuresis with reduced hyperkalaemia compared with steroidal antagonists, potentially provides anti-inflammatory and antifibrotic effects in DKD [153]. Finerenone inhibits MR over-activation and has recently been shown to slow the progression of CKD and reduce the risk of CV events in T2D [173]. In addition, preclinical studies have demonstrated the anti-inflammatory effects of SGLT2 inhibitors empagliflozin and dapagliflozin in association with a reduction in albuminuria and renal fibrosis in DKD [174,175].…”
Section: Agents Targeting Inflammation Oxidative Stress and Fibrosismentioning
confidence: 99%